Projeto e implantação de sistema fotovoltaico autônomo para iluminação pública baseada em led - RODRIGUES, Mayara Pereira (2024)
Currently, the issues addressing the issue of energy are gaining more space on the world stage, by several factors: the most used energy sources are causing great social and environmental damage, for example, severe air pollution with carbon dioxide, from the burning of fossil fuels; due to the large energy consumption, the blackouts is becoming more frenquentes, allowing the lack of public safety; many people still have no access to public lighting systems; among others. In this context, the need arises for new energy alternatives that meet the human need for energy and reduce the problems currently presented, in order to consolidate sustainable development. Thus, this paper aims to present a retrieval power project using solar energy, a renewable source of energy that is emerging on the global stage. The application of this work takes place in the street lighting system, since that demand considerable consumption of electricity, as in Brazil, for example, where corresponds to 3.0% of all consumption. Therefore, the project consists of a photovoltaic system that is independent of the power grid, consists of Photovoltaic Panel 55 W, stationary battery life for 2 days without power generation operation, charge controller with pre-programmed timer (who also serves as the photoelectric relay function), set of LEDs (Light Emitting Diodes) 10 W equivalent to 70W conventional sodium vapor lamp and works fully in DC and 12 V voltage, eliminating thus the use of voltage inverter. Furthermore, the design of the structure which supports the components was carried out in software and provides a novel, unique design. His electrostatic powder paint, needs no chemical solvents and has a durability to weather